2018
DOI: 10.3389/fphys.2018.01817
|View full text |Cite
|
Sign up to set email alerts
|

Menthol Cigarette Smoke Induces More Severe Lung Inflammation Than Non-menthol Cigarette Smoke Does in Mice With Subchronic Exposure – Role of TRPM8

Abstract: In smokers with chronic obstructive pulmonary disease, more severe lung inflammation is associated with menthol cigarette smoking compared to non-menthol cigarette smoking. However, the mechanisms remain unclear. Menthol is an activator of transient receptor potential melastatin-8 (TRPM8), which is also sensitive to reactive oxygen species (ROS). Our recent in vitro study demonstrated that the extracts of menthol cigarette smoke (M-CS) can induce greater ROS-sensitive, TRPM8-mediated, mitogen-activated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…In our study, superoxide production was found significantly increased in mouse lung tissues harvested 2 hours after the 1 hour ACS exposure, and most dramatically increased at 6 hours post exposure. Our data indicate a time-dependent production of superoxide in ACS exposed mouse lung tissues, which is consistent with previous observations evidencing ACS induction of superoxide and hydrogen peroxide accumulation in BAL fluid [ 35 ]. Of note, here, we elucidated that Puerarin dose-dependently abolished ACS induced superoxide production in the mouse lung tissues.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, superoxide production was found significantly increased in mouse lung tissues harvested 2 hours after the 1 hour ACS exposure, and most dramatically increased at 6 hours post exposure. Our data indicate a time-dependent production of superoxide in ACS exposed mouse lung tissues, which is consistent with previous observations evidencing ACS induction of superoxide and hydrogen peroxide accumulation in BAL fluid [ 35 ]. Of note, here, we elucidated that Puerarin dose-dependently abolished ACS induced superoxide production in the mouse lung tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Further, a large proportion of youth preferentially consume flavored nicotine products, with menthol as one of the most popular for tobacco cigarettes ( Jackson et al, 2020 ; Villanti et al, 2017 ). In smokers with chronic obstructive pulmonary disease, more severe lung inflammation is associated with menthol cigarette smoking compared to non-mentholated products ( Park et al, 2015 ), and in mice, sub-chronic exposure to the extracts of menthol cigarette smoke induces lung inflammation ( Lin et al, 2018 ). Although the putative action of menthol and other flavorants on ACE2 has not yet been elucidated, one may predict that menthol would act synergistically with nicotine to exert detrimental effects, although this needs to be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pure menthol was cytotoxic to bronchial epithelium at the concentrations found in EC products when tested in vitro with the MTT assay using 2D submerged cell cultures (Behar et al, 2017;Hua et al, 2019). Lin et al, (2018) showed that subchronic exposure of mice to mentholated cigarette smoke induced more inflammation in lungs than smoke from nonmentholated cigarettes. Recently, serious respiratory illness and death have been attributed to EC use, and patients requiring hospitalization have been reported to have "e-cigarette or vaping product use-associated lung injury" (EVALI) (Centers for Disease Control and Prevention, 2019).…”
Section: Introductionmentioning
confidence: 99%